Fiji Education Management Information Systems : SABER Country Report 2017 - Saraogi, Namrata; Mayrhofer, Diana Katharina; Abdul-Hamid, Husein (World Bank, Washington, DC, 2017)
In 2011, the World Bank Group commenced a multiyear program designed to support countries in systematically examining and strengthening the performance of their education systems. this evidence-based initiative, called systems approach for better education results (SABER), uses diagnostic tools for examining education systems and their component policy domains against global standards and best practices and in comparison, with the policies and practices of countries around the world. By leveraging this global knowledge, the SABER tools fill a gap in the availability of data and evidence on what matters most to improve the quality of education and achievement of better results. This report discusses the results of applying the SABER - education management information systems (EMIS) tool in Fiji. The objectives of this report are to examine the system according to key policy areas, identify successes, and challenges in the system, and provide recommendations to support the continued advancement of EMIS in Fiji.